Tensor Effects in Dipole Excitations at Finite Temperature - Yuksel, E.; Bozkurt, K. (POLISH ACAD SCIENCES INST PHYSICS, 2013)
Tensor effects in the dipole excitation of neutron-rich Ni-68 nucleus are investigated in the framework of Skyrme-Hartree-Fock plus random phase approximation at finite temperature. We calculate isovector giant and pygmy dipole strengths with finite temperature random phase approximation by using different tensor correlations. The effect of both tensor and finite temperature on the giant dipole resonance-pygmy dipole resonance energy region is analysed. Pygmy dipole resonance calculations with different proton-neutron tensor coupling constants are also compared with the experimental results. DOI: 10.12693/APhysPolA.123.320
Keywords: NUCLEI; RESONANCE; SN-120; STATES; Physics